The methodology of Maurice Hauriou : legal, sociological, philosophical - Gray, Christopher B. (Value Inquiry Book Series, 2010)
This book shows that Hauriou's positivist and pragmatic jurisprudence and social theory, as well as their application to the study of institutions, is satisfactorily supported by his idealistic philosophy. The nine chapters first locate Hauriou's influences, then situate his disciplinary methodologies within methodology in general. The central chapters concern each of the three methodologies in turn.